Avaliação nutricional do jundiás frente a dietas contendo diferentes níveis de arginina e seu antagonismo lisina/arginina - Maschio, Daniel (2013)
The objective of this study was to evaluate the optimum addition level of arginine and the relationship of antagonism between amino acids arginine and lysine in diets for juvenile south brazilin catfish (Rhamdia quelen) for variables that were studied live performance, composition and nutrient retention, biochemical parameters , liver and digestive. The first trial lasted 45 days, was conducted in the fish farming Laboratory of Federal University of Santa Maria, in water recirculation system, using 24 280 l tanks, each equipped with two experimental units (cages with useful volume of 15 l), each unit was populated with 12 fish (initial weight of 2.00 ± 0.04 g). The experimental design was completely randomized in a factorial arrangement of two for six, and to 4.5% and 5.1% lysine were used following arginine levels: 2.5, 3.0, 3.6, 4, 3, 5.0 and 5.6%, totaling 12 treatments with 4 replicates. The second experiment lasted 49 days, following the same methodology as the first varying levels of inclusions arginine, lysine content keeping fixed at 6.65% of the protein fraction, testing six increasing levels of arginine: 4.20, 4.65, 5.0, 5.35, 5.65 and 6.00% each with four replications. Each unit was populated with 15 fish (mean weight 0.3 ± 3.00 g). In the first study based on the results obtained by polynomial regression equations, we conclude that the combination of 5.1% to 4.6% lysine with arginine provided better performance associated with greater carcass yield and lower body fat deposition. The second study that remained fixed in 6.65% lysine (protein), found better response to the inclusion of 5.8% arginine in the protein fraction of the diet.